"A Man Can Start over Again" - on the Separation as a Requirement for Good - Danuta Wajsprych (Nicolaus Copernicus University in Toruń, 2014)
The article seeks an answer to the question about meaning, sense and role of separation category in the existential experience of man. The analyses refer to Tischner's ethical project, defined by the author as agatological pedagogy, specifically to the part where Tischner perceives separation as one of the requirements for possibility of occurrence of good in relationship with the Other. Tischner perceived good as infallible tool in revealing both agathological and axiological dimension of human existence, as well as in recognizing the crisis generating human suffering, therefore the idea of good triumphing over evil in human existence became Author's primary duty.